Psychometric properties of the Confidence and Trust in Delivery Questionnaire (CTDQ): a pilot study - Jeschke Elke; Ostermann Thomas; Dippong Natalie; Brauer Dagmar; Matthes Harald (BMC, 2012)
Abstract Background Assessing expecting mother's opinions prior to birth draws a comprehensive picture for the caregivers about their emotional state and their expectations. Some questionnaires to cover these aspects do exist. This study aims to present the psychometric properties of a new instrument, the Confidence and Trust in Delivery Questionnaire (CDTQ) a short but reliable a self-report instrument that focuses on confidence and trust as meaningful dimensions for expectant mothers. Methods A pilot validation study of 221 women 6 weeks before childbirth was conducted in Germany between October 2007 and June 2008. To detect structural relations between the items, factor and reliability analyses were applied to the CTDQ items. Factor analysis was performed by means of principal components analysis and varimax rotation. Internal reliability was assessed by Cronbach's alpha. External validation was performed using the sense of coherence (SOC) scale. Results The CTDQ comprises of 11 items. We found a 4-factor structure. The internal consistency of the whole item pool (Cronbach's α = 0.79) and the 4 subscales [confidence in labor (α = 0.82); partner's support (α = 0.62); trust in medical competency (α = 0.68); being informed (α = 0.60)] can be regarded as sufficient or even excellent. The 4 factors explained 69.6% of total variance. Except for a high intercorrelation (0.70) between "partner's support" and "trust in medical competence", the subscales show low intercorrelations, indicating an adequate independence of the respective subscales. Regarding the external validity we found minor respective moderate correlations with the SOC scale. Conclusions Our data suggest that the CTDQ is a useful instrument to assess confidence and trust in delivery. With 4 clinically relevant dimensions, the CTDQ is now open for further studies in the field of labor.